As contribuições de Paramahansa Yogananda à Educação Ambiental Holística - Superando a fragmentação do Pensamento do Sujeito na Ação Ambientalista - Oliveira, José Arnóbio Albuquerque de (2007)
The aim of this work is to present an updated reflection concerning the state of environmental ecological problems through a deep and wide-ranging bibliographical research. In search to understand how molded the values which influence the collective mentality was it was found in many authors who studied the questions of the paradigms consistent answers on the sense of current existence. It was then understood that the Cartesian paradigms, inaugurated by René Descartes (1596-1650), support an existential model of fragmentary and disintegrated character which predominates in the present Era and whose tendency is the irrational exploitation of natural resources. The quantum paradigm, which is an important theoretical reference for the holistic perspective, has constituted an emergent conception since the discovery of physics in the early twenties and it also points at a balanced use of natural resources without any risk to the surviving of ecosystems which support life in our Planet. The main goal of this research was to investigate the potential of contribution of the Indian educator Paramahansa Yogananda to Environmental Education, in the elaboration of a cosmo vision which is able to guide the human conscience to the understanding of his integrated nature mediated by a scientific non-dogmatic and non-sectarian pedagogy, in order to orient the human being for a balanced usufruct of natural resources. The conclusion was that his "how to live school", which is based on the principles of the science of yoga, has the potential of attending such requisites.